The ethics of Husserl's phenomenology : responsibility and ethical life - Siles i Borrás, Joaquim (Continuum studies in continental philosophy., 2010)
The Ethics of Husserl''s Phenomenology aims to relocate the question of ethics at the very heart of Husserl''s phenomenology. This is based on the idea that Husserl''s phenomenology is an epistemological inquiry ultimately motivated by an ethical demand that pervades his writing from the publication of Logical Investigations (1900-1901) up to The Crisis of European Sciences and Transcendental Phenomenology (1935). Joaquim Siles-Borràs traces the ethical concepts apparent throughout Husserl''s main body of work and argues that Husserl''s phenomenology of consciousness, experience and meaning i.